Deconstruction of Wikipédia Jawa as the Source of Javanese Online Information - Evelin Giovani; Sri Winarsih; Marnina (Technium Social Sciences Journal, 2023)
This study aims to deconstructed Wikipédia Jawa as a source of reference for Javanese article using Derrida’s deconstruction theory. Wikipédia Jawa is one of the Wikipedia projects along with local communities in the world to re-popularize local languages that are empowered for free through internet. This research begins by reading the Wikipédia Jawa website through text which was profided on the page then delays the meaning by searching for the deeper meaning in the website through context and co-text. The hypothesis of this study is Wikipédia Jawa loses its simpleness and easy-to-understand values that cling to ‘Wikipedia’ itself. Wikipédia Jawa as a source of reference for online information in Javanese uses high level of Javanese, Bahasa Jawa Krama, which makes it more difficult for general readers to understand the articles. Furthermore, Wikipédia Jawa only can be consumed by small community which provokes exclusivity of society members.